Comparative population dynamics of zebra mussel (Dreissena polymorpha) populations in two similar closely adjacent warm-water Texas reservoirs - Jason L. Locklin; Josiah S. Moore; Robert F. McMahon (Aquatic Invasions, 2024)
Zebra mussel (Dreissena polymorpha) population dynamics were recorded between 2 September 2019 and 26 September 2020 at marina sites in each of two adjacent central Texas water bodies, Belton (BL) and Stillhouse Hollow (SHL) Lakes infested in 2013 and 2016, respectively. Lake water temperatures were insignificantly different while dissolved oxygen, pH and Secchi Disk depths were slightly higher in SHL. Veliger densities in both populations peaked in late Fall 2019 with veligers becoming absent by January 2020. Veliger densities again peaked in May-August 2020. These fall and spring spawning periods resulted in the presence of fall and spring mussel settlement cohorts. Mussel densities on settlement plates were greater at SHL than BL. At both sites, Fall 2019 cohorts had a lifespan of approximately one year or less, experiencing mass mortality during peak water temperatures in late summer/early fall the year after initial cohort settlement. Shell growth rates of the Spring 2020 BL and SHL cohorts were 91.4 and 67.3 µm/day, over a 126 day growing period, respectively, falling within the range reported for mussel populations in other southwestern US water bodies. Rapid shell growth and maturation allowed initiation of spawning earlier than zebra mussel populations in cooler, higher latitudes. Rapid growth and early maturity allows southwestern US zebra mussel populations to rapidly attain peak densities after infestation followed by population declines as recorded in BL. That southwestern mussel populations rapidly attain post invasion peak densities allows little time for water using facilities to develop effective, environmentally acceptable means of protecting infrastructure from mussel fouling. Thus, plans to prevent/minimize mussel fouling should be made in advance of invasion. Similarly, water body managers should develop and implement plans to minimize invasion likelihood and for rapid response before invasion occurs.